The burden of lung cancer in Latin-America and challenges in the access to genomic profiling, immunotherapy and targeted treatments. (May 2018) - Raez, Luis E.; Cardona, Andrés F.; Santos, Edgardo S.; Catoe, Heath; Rolfo, Christian; Lopes, Gilberto; Barrios, Carlos; Mas, Luis A.; Vallejos, Carlos; Zatarain-Barrón, Zyanya Lucia; Caglevic, Christian; Arrieta, Oscar
Highlights: Lung cancer is still the first cause of cancer-related deaths in Latin America. Regional challenges include the optimal implementation of tobacco control policies. Differences in healthcare, diagnostic and treatment options generate inequality. Breaching the gap between the best care available and the current care is adamant. Regional based research and education programs seek to improve the current outlook. Abstract: Lung cancer is a public health problem worldwide and Latin America (LATAM) cannot escape this reality. This malignant disease has not only a high prevalence in the region, but is also the main cause of cancer related deaths, and in other emerging countries, the incidence rates are still on the rise. Interestingly in most LATAM countries, lung cancer mortality has been decreasing in men but not in women, reflecting smoking patterns in countries such as Chile, Bolivia, and Brazil. Despite the fact that these issues are well known to government agencies, physicians and patients in the region, current efforts still fall behind those needed in order to face this problem of epidemic proportions. Tobacco control and smoking cessation are the most important interventions against lung cancer, but even with their optimal implementation (which is far from reality at this time) the number of cases in the foreseeable future would still be significant. Beyond tobacco control, advances in our understanding of the molecular component of lung cancer have resulted in new targeted therapies and immune check point inhibitors, which have improved clinical outcomes but at a considerably higher financial cost. LATAM has not widely and speedily adopted these strategies, including new technology and approved novel drugs, due to a number of facts, and therefore only a dismal proportion of LATAḾs patient population have benefited from these new advances. A keen focus on a heterogeneous education system for caregivers in lung cancer treatment would likely help standardize care and improve future potential gains from domestic research. In this review we discuss the challenges of treatment implementation, focusing on new technologies.